2011
DOI: 10.1007/s00397-011-0613-7
|View full text |Cite
|
Sign up to set email alerts
|

Wall slip and melt fracture of poly(lactides)

Abstract: The wall slip and melt fracture behaviour of several commercial polylactides (PLAs) as well as their rheological properties under shear and extensional have been investigated. The PLAs have had weight-average molecular weights in the range of 10 4 -10 5 g/mol and studied in the temperature range of 160-200 • C. The solution properties and linear viscoelastic behaviour of melts indicate linear microstructure behaviour. PLAs with molecular weights greater than a certain value were found to slip, with the slip ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 49 publications
2
35
1
Order By: Relevance
“…14 shows the dependence of ''R h '' on the average molecular weight Mw for the neat and modified PLA with Joncryl, compared to the scaling relation Rh ¼ 0:017 Â Mx 0:56 for monodisperse and linear PLA [27]. It can be noticed that the data of the modified samples diverge from the reported results by the relation since Joncryl is added in the system.…”
Section: Solution Viscometry and Physico-chemical/structural Propertiescontrasting
confidence: 53%
“…14 shows the dependence of ''R h '' on the average molecular weight Mw for the neat and modified PLA with Joncryl, compared to the scaling relation Rh ¼ 0:017 Â Mx 0:56 for monodisperse and linear PLA [27]. It can be noticed that the data of the modified samples diverge from the reported results by the relation since Joncryl is added in the system.…”
Section: Solution Viscometry and Physico-chemical/structural Propertiescontrasting
confidence: 53%
“…mg.mL -1 were prepared in THF for each polymer and injected sequentially to construct a curve with slope dn.dc -1 [24]. The refractive index values for PLA, PLA-TAM, and PLA-GMA were determined to be 0.0482 ml.gm -1 , close to values reported in the literature [25].…”
Section: Foam Characterizationmentioning
confidence: 99%
“…It has been reported that PLAs with molecular weight greater than a certain value exhibit slip [12]. This might be expected due to their linear structure and similarities with other linear molecules that exhibit slip and melt fracture [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 93%
“…The K-BKZ constitutive equation was used to model the rheological data satisfactorily, including strain hardening which might occur in spite of the linear macrostructure of these polymers [7,11]. The processability of PLAs has also being studied in the literature, particularly its processing as can be assessed by melt fracture phenomena [12][13][14]. Ways to eliminate melt fracture instabilities in the capillary flow of PLAs have been reported in detail by Jazrawi et al [14] using methods previously developed for polyethylenes [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation